Divergence With Gene Flow and Contrasting Population Size Blur the Species Boundary in Cycas Sect. Asiorientales, as Inferred From Morphology and RAD-Seq Data - Chang, Jui-Tse; Chao, Chien-Ti; Nakamura, Koh; Liu, Hsiao-Lei; Luo, Min-Xin; Liao, Pei-Chun (Frontiers in Plant Science, 2022)
Incipient species are an interesting part of studying speciation. However, due to incomplete lineage sorting or gene flow, the divergence process is difficult to illuminate. Together with fragmented distribution and morphological conservatism, species taxonomy is also challenging without comprehensive sampling and combination of different data. Cycas sect. Asiorientales, which includes only Cycas taitungensis and Cycas revoluta, is mainly distributed along the fragmented Ryukyu Arc. The two species are inferred to be recently diverged with continuous gene flow and paraphyly; however, their large genome size questions the previous evolutionary inferences because there are few genetic markers and sampling has been incomplete. In addition, their comprehensive morphological comparison is lacking due to long-term taxonomic misconception. Here, by sampling the whole range of these species, we used genome-wide single nucleotide polymorphisms (SNPs) to test the geographic mode of speciation in Cycas sect. Asiorientales by approximate Bayesian computation. The individual tree was reconstructed to delimit the species and capture the historical gene flow pattern. We also reexamined the diagnostic morphological traits to compare with genetic data. Our results demonstrated recent non-allopatric speciation with continuous gene flow and contrasting population size between the species. Moreover, the gene flow would be spatially heterogeneous as driven by transoceanic vegetative dispersal. These historical events have contributed to larger intraspecific than interspecific variations in morphogenetic patterns between C. revoluta and C. taitungensis and have blurred their species boundary. The synonymized treatment on these Cycas with geographically structured genealogy has highlighted the disadvantage of species as the conservation unit and the importance of the Kuroshio Current for species evolution.